(3OjhGf GHf GdeYde GdhGSWjs - (3CHhGdZfGFe fLe GdOjf eMeO Hf Ydj Hf aGQS GdgQKj GdhGSWj, GHf GdeYde,J (B592 (3g` s ((3GdMSf Hf LGHQ Hf CMeO Hf Ydj GdSejMj s)
(3ChdgG (B:s
(3aCjf GdSdGeI ef YGTb dg aj Gdghi TZd TGZd s
(3BNQgG (B:s
(3cGfhG hHGfhG hgh fhQ GdgOi hdOi GdrO oOfjG hge eYTQ cGfhG heG HGfhG s
(3fSNI KGdKIs
(3hbO oCdMbJ HBNQ GdfSNI bUGFO dCHf GdJYGhjPj hGdTQja GdQVi HfaS GdNWs
(3HQSe GdMSjf Hf GdMSf Hf GdbGSe CejQ GdeDefjfs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs